2020
DOI: 10.1002/humu.24055
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the complex architecture of ALS in Turkey: Expanding genotypes, shared phenotypes, molecular networks, and a public variant database

Abstract: The last decade has proven that amyotrophic lateral sclerosis (ALS) is clinically and genetically heterogeneous, and that the genetic component in sporadic cases might be stronger than expected. This study investigates 1,200 patients to revisit ALS in the ethnically heterogeneous yet inbred Turkish population. Familial ALS (fALS) accounts for 20% of our cases. The rates of consanguinity are 30% in fALS and 23% in sporadic ALS (sALS). Major ALS genes explained the disease cause in only 35% of fALS, as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Homozygous variants in the OPTN gene were already described in Turkish familial ALS patients, including the variant outlined in the current study. Similar to our index patients, the reported cases exhibited an early age of onset but were solely associated with a typical ALS phenotype only, without FTD 24 . Another recent study reported on a case with parkinsonism and corticobasal syndrome (CBS) in association with a heterozygous OPTN frameshift insertion, 3 and yet another study of familial ALS revealed two Tunisian siblings with a clinical phenotype of ALS‐CBS and a homozygous OPTN mutation, 28 further underlining the heterogeneous phenotype–genotype correlation.…”
Section: Discussionsupporting
confidence: 83%
“…Homozygous variants in the OPTN gene were already described in Turkish familial ALS patients, including the variant outlined in the current study. Similar to our index patients, the reported cases exhibited an early age of onset but were solely associated with a typical ALS phenotype only, without FTD 24 . Another recent study reported on a case with parkinsonism and corticobasal syndrome (CBS) in association with a heterozygous OPTN frameshift insertion, 3 and yet another study of familial ALS revealed two Tunisian siblings with a clinical phenotype of ALS‐CBS and a homozygous OPTN mutation, 28 further underlining the heterogeneous phenotype–genotype correlation.…”
Section: Discussionsupporting
confidence: 83%
“…In screening known ALS genes for variants in familial ALS cases from Germany, Muller et al demonstrated phenotype/genotype correlations with previously reported as well as described novel variants in known genes 3 . A Turkish ALS population study found that 45% of familial ALS and 10% of sporadic ALS patients carried a variant in a previously reported gene; somewhat less than other European population screenings, indicating that differences between relatively close geographic regions can impart substantial effects on panel screening utility 4 . For example, in this Turkish cohort, expansion in C9orf72 was the most common observed variant, but at a rate lower than expected based on Northern European prevalence estimates.…”
Section: Introductionmentioning
confidence: 93%
“…Altogether, these findings suggest a greater role for A3 in ALS pathogenesis than just HR and DPR regulation. However, despite both A1 and A2/B1 carrying missense mutations associated with ALS and neurodegenerative diseases [51,188], no single nucleotide variations in HNRNPA3 in ALS patients (familial and spontaneous) have been detected in cohort screening studies [288,295,296].…”
Section: Neurobiologymentioning
confidence: 99%